(untitled) (Revista Innova Educación, 2024)
Mathematics are fundamental in various areas of science, and although teaching it presents challenges, using technology in the classroom offers an opportunity to enhance the learning process, allowing a deeper understanding of concepts and their application in real contexts. In light of this, the current research evaluated the effectiveness of the PhET simulator in teaching the topic of graphing quadratic functions to upper secondary students, aiming to identify the impact of this educational technological tool on their learning. The study was quantitative with a descriptive scope and a pre-experimental design. Prior to the implementation of the treatment, a written questionnaire was applied to students in their fourth semester at Conalep Plantel Tizimín (Yucatan – Mexico), which served to measure their knowledge on the subject under study. After the treatment, the questionnaire was reapplied, along with an opinion survey in which the students expressed their views on the use of the PhET simulator. The results indicated that the use of the PhET simulator significantly improved the understanding of the topic of graphing quadratic functions, with an average increase of 17.33% in student grades (p<0.05). In conclusion, the implementation of the PhET simulator in teaching quadratic functions significantly improves academic performance and, in turn, increases students’ interest in using technological tools.